The Love, Theology, and Religious Moderation: A Critical Analysis of Haidar Bagir’s Islamic Thought - Harda Armayanto; Erni Puryati Ningsih; Fasya Tharra Annada; Riski Melanie; Amir Sahidin (Indonesian Journal of Islamic Literature and Muslim Society, 2026)
The association of Islam with intolerance and radicalism has contributed to negative perceptions of the religion, despite Islam’s essential mission as raḥmatan lil-‘ālamīn. In response to this problem, Haidar Bagir proposes the concept of the Religion of Love, which emphasizes love, compassion, and spirituality as central dimensions of Islamic teaching. This study critically examines Bagir’s concept and evaluates its theological implications for Islamic creed (‘aqīdah). Using a qualitative library research method, the study analyzes Haidar Bagir’s works, relevant literature on Islamic mysticism and theology, and critical responses from contemporary Muslim scholars. The data are examined through descriptive-analytical and critical approaches by comparing Bagir’s views with classical Islamic theological perspectives and the Indonesian Ulama Council’s fatwa on religious pluralism. The findings show that the Religion of Love offers a constructive contribution to presenting Islam as peaceful, moderate, and compassionate. However, if not carefully framed, the concept may be misinterpreted as religious relativism, particularly when love is detached from the principles of tawḥīd and Islamic law. This study concludes that the Religion of Love can serve as an effective approach to countering intolerance and radicalism, provided that it remains firmly grounded in Islamic theological foundations.